KONTRIBUSI PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA BITUNG - Majampoh, Christian Ferdinand; Elim, Inggriani; Suwetja, I Gede (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Law no. 32 of 2004 on Local Government to determine local taxes one source of revenue coming from the region. For that we need to examine how big the contribution of restaurant tax to PAD Bitung City. Local taxes are divided into two parts: provincial tax and city / county tax. One type of city / district tax is Restaurant Tax. This study aims to determine the contribution of restaurant tax Bitung City. Research method used in this research is descriptive analysis method. The object of research is taken at the Office of Regional Tax and Retribution Board of Bitung City. This study shows the calculation by using the contribution analysis can be seen that the contribution of restaurant tax Bitung city in the period 2013 - 2017 decreased. The rate of growth of restaurant tax in the early period had experienced a growth in restaurant tax revenues despite the last year (2017) there was a very significant decrease so that the value is negative. This study shows that Bitung City Government has not been able to reach the target that has been determined, this is because not yet maximum supervision from the Office of Revenue Management Finance and Regional Assets Bitung City in levy restaurant tax, so there are still many restaurants that do not pay taxes. The conclusion obtained is the analysis of restaurant tax contribution in the City of Bitung in the year 2013 amounted to 2.41% and there was a decrease in 2017 to become 1.09%. For that Bitung City Local Government should be more firm and pro active again in levy restaurant tax.Keywords: Restaurant Tax, PAD